Adherence to apixaban for extended thromboprophylaxis after major abdominal or pelvic surgery for cancer: A prospective cohort study. Issue 2 (1st April 2022) - Schulman, Sam; Carlson, Vanessa; Serrano, Pablo E.; Sne, Niv; Kahnamoui, Kamyar; Mithoowani, Siraj; Ikesaka, Rick; Gross, Peter L.
Abstract: Background: Due to lack of data, direct oral anticoagulants are not considered by guidelines for venous thromboembolism (VTE) prophylaxis after cancer surgery. Adherence to low‐molecular‐weight heparin injections in this setting is sometimes poor. Aim: Analysis of adherence to oral apixaban for extended thromboprophylaxis. Methods: Consecutive patients discharged after major surgery for abdominal/pelvic cancer and considered eligible for extended prophylaxis were offered apixaban 2.5 mg twice daily. Primary outcomes were adherence metrics—proportion of prescriptions filled, persistence (not prematurely discontinued), proportion of days covered (PDC) based on apixaban pill counts, and modified Morisky medication adherence scale at Days 28–30. Secondary outcomes were bleeding, VTE, and serious adverse events until Day 90. Results: We included 53 patients, 51 were analyzed. Of 45 patients with prescriptions all had it filled (95% confidence interval [CI], 92%–100%). Persistence was 98% (95% CI, 90%–100%). PDC was ≥80% for 48 patients (94%; 95% CI, 84%–99%). We found good adherence (0/6 answers "yes") in 75% and moderate (1/6 answers "yes") in 25%. No major bleed or VTE occurred while on apixaban. Conclusion: Our results support good adherence with apixaban for VTE prophylaxis up to 28 days after major abdominal or pelvic cancer surgery.